Psycholinguistic Representation of Individual Traumatic Memory in the Context of Social and Political Ambiguity - Zasiekina, Larysa (East European Journal of Psycholinguistics, 2014)
The paper focuses on a psycholinguistic study of individual traumatic memory. Among psycholinguistic tools of the research are psychographological analysis, propositional analysis, and frame analysis. The results of psychographological analysis revealed differences between psycholinguistic representations of traumatic events as compared to psycholinguistic representation of neutral events in norm for written speech. Higher psychographological indices in representation of traumatic events show the emotional lability (high sentence length), low awareness and meaningfulness of the event (high quotient of logical coherence), and low motivation (small number of words in the narratives). Frame analysis allowed revealing distribution of traumatic events in the context of political and social ambiguity. Propositional analysis showed  distribution of  propositional elements in the narration of traumatic events, which express  the meaning of traumatic events in a person’s life (attitude);  significance of external circumstances in the awareness of the traumatic event (external object); the main participants of the traumatic event (external argument); the narrator and his/her role in the traumatic event (internal argument); low importance of localization and chronological order of the traumatic event (context); the  secondary (passive) role of narrator in the traumatic event and emphasizing the importance of the external circumstances (internal objects). The results of T-test show the differences in psycholinguistic representation of traumatic memory  between two samples: respondents without PTSD  (95 people) and respondents with PTSD and tendencies to PTDS (111 people). The narrators of the second sample (with PTSD) have higher indices of norm deviations in psychographological analysis, a higher percent of the attitude and internal argument in the predicate in propositional analysis, lower variety of frame clusters of traumatic events than narrators of the first sample (without PTSD).ReferencesAlvarez-Conrad J., Zoellner L. A., Foa E.B. (2001). Linguistic predictors of trauma pathologyand physical health. Applied Cognitive Psychology, 15(7), 159–170.Anderson, J. R., Bower, G. (1974). Propositional theory of recognition memory. Memory &Cognition, 2(3), 406–412.Barclay, C.R. (1996). Autobiographical Remembering: Narrative Constraints on ObjectifiedSelves. Remembering our Past, 94–128.Bremner, J.D. (2001). Hypothesis and controversies related to effects of stress on thehippocampus: An argument for stress-induced damage to the hippocampus in patients withposttraumatic stress disorder. Hippocampus, 11, 75–81.Colman, A. (2003). Oxford Dictionary of Psychology. Oxford: Oxford University Press.Garcia D., Sikström S. (2013).Quantifying the semantic representation of adolescents’memories of positive and negative life events. Journal Happiness Study, 14,1309–1323.Foa E., Molnar, C., Cashman L. (1995). Change in rape narratives during exposure therapy forposttraumatic stress disorder. Journal of Traumatic Stress, 8, 675–690.Fornberg, E. (1997). Amygdala, Emotions, Motivation and Depressive States. (pp. 301–333).In, R. Plutchnik and H. Kellerman (Eds.), Emotion: Theory, Research, and Experience, 3.Herman, J. (1997). Trauma and Recovery: The Aftermath of Violence – from Domestic Abuseto Political Terror. Cambridge, Mass.: MIT Press.Klein, K. (2002). Stress, Expressive Writing and Working Memory. The Writing Cure: HowExpressive Writing Promotes Health and Emotional Well-being. Washington, D.C.: AmericanPsychological Association.Marshall, R. D., Turner, J. B, R. Lewis-Fernandez, R. (2006). Symptom patterns associatedwith chronic PTSD in male veterans: new findings from the National Vietnam Veterans ReadjustmentStudy. Journal of Nervous and Mental Disease, 194 (4), 275–278.Meichenbaum, D. A. (2004). Clinical Handbook for Assessing and Treating Adults with PostTraumatic Stress Disorder (PTSD). Waterloo: Institute Press.Pennebaker, J.W., Francis, M.E. (1996). Cognitive, emotional and language processes indisclosure. Cognition and Emotion, 10, 601–626.Shapiro F. (2001) Eye Movement Desensitization and Reprocessing. NY : Guilford.Taylor, S. (2006). Clinican’s Guide to PTSD: A Cognitive-Behavioral Approach. Guilford:Guilford Press.Tulving, E. (1972). Episodic and Semantic Memory. New York: Academic Press.Watzlawick, P., Weakland, J. H., Fisch, R. (1974). Change: Principles of Problem Formationand Problem Resolution. Oxford: Oxford University Press.Yehuda, R.B., Kahana, K., Binder-Byrnes S.M., Woutwick, J.M.,Giller, E.L. (1995). Lowurinary cortisol excretion in Holocaust survivors with posttraumatic stress disorder. American Journal ofPsychiatry 152, 982-986.Zasiekina, L. (2012). Psykholingvistychna reorhanizatsia travmatychnoyi pamiati zperspektyvy psykhichnoho zdorovia [Psycholinguistic reorganization of traumatic memory from theperspective of individual psychic health]. Visnyk of National Academy of Border Service of Ukraine,Retrieved from http://archive.nbuv.gov.ua/ejournals/Vnadps/2012_1/12zlvpzo.pdfZasiekina, L., Zasiekin, S. (2008). Psykholinhvistychna Diahnostyka [PsycholinguisticDiagnostic]. Lutsk: Vezha.
Keywords: traumatic memory; post-traumatic stress disorder; psycholinguistic representation of traumatic memory; psychographological analysis; propositional analysis; frame analysis.